The effect of different grain sizes and heat input on the gas pressure inside artificial resin-bonded sand cores. Issue 1 (August 2020) - Mádi, L; Budavári, I; Varga, L
Abstract: Sand cores are used to form the cavities of the castings. The quality of castings is directly affected by the quantity of the gases released from the cores. During our research, the effect of different grain sizes and heat input on the pressure of the gases evolved from the cores was investigated. The granulometric properties of the sand used for making the cores have a significant impact on the pressure of the gases. Because of the uneven particle size distribution of multi fraction sands, the gas flow conditions in the cores can be different. The gas pressure in the cores made from sieved sands can be changed between 6 and 9 mbar. According to the recorded cooling curve of the melt, it can be established, that in the case of the presented pouring conditions, a solid metal layer with adequate strength could not be developed before the gas could pass through the core/casting interface. This phenomenon may result in gas blowhole defects on the casting surface.